Exploring mental health symptoms in elite athletes during the COVID-19 pandemic: A systematic review and meta-analysis on sex differences - Liang-Tseng Kuo; Sung-Huang Laurent Tsai; Udit Dave; William A. Marmor; Reena Olsen; Bridget Jivanelli; Michelle E. Kew; Daphne I. Ling (PLoS ONE, 2025)
The COVID-19 pandemic significantly affected elite athletes, leading to increased mental health issues such as stress, anxiety, and depression. Sex differences in mental health may exist among athletes during the COVID-19 crisis. This study aimed to perform a systematic review and meta-analysis to examine sex differences in mental health symptoms among elite athletes during the COVID-19 pandemic. We systematically searched the databases including Pubmed, EMBASE, and manually checked previous systematic reviews for relevant studies in March 2024. Authors were also contacted for sex-specific data. Studies were included if they compared mental health symptoms between male and female elite athletes during the COVID-19 pandemic. We used a random-effects model to summarize the rate ratio (RR) between female and male athletes across studies. Risk of bias in studies was assessed using a 9-item tool. We included 18 studies in this review. The results indicated that female athletes reported higher levels of anxiety (RR 1.24, 95% CI = 1.08 to 1.43) and depression (RR 1.36, 95% CI = 1.15 to 1.61) than male athletes during the pandemic. They also had a higher risk of stress or distress (RR 1.27, 95% CI = 0.99 to 1.63) than their male counterparts. No significant differences were found regarding alcohol use or misuse between female and male athletes (RR 1.01, 95% CI = 0.75 to 1.37). Limited evidence was available for eating disorders, gambling, substance use, and sleep problems. In conclusion, female and male athletes differed in mental health symptoms during the COVID-19 pandemic. Female athletes were more likely to report anxiety, depression, and distress. Incorporating mental health resources may be particularly important for women’s sports, which have smaller financial margins and greater career uncertainty than men’s sports.